Microbial Diversity in Rhizosphere Soils of Tropical Tuber Crops: Utilization for Pathogen Suppression and Growth Promotion - Aswathy B, Nair; S. S., Veena; M. N., Sheela; S., Karthikeyan; G. L., Sreelatha; V. R., Vishnu (JOURNAL OF ROOT CROPS, 2019)
Tuber crops are the third most important food crops, after cereals and legumes. There are many pathogenic microbes, which affect the production of tuber crops. Fungal and viral pathogens attack most of the tuber crops. However, there is much variability among the crops in their susceptibility to pathogens. Similarly, rhizosphere soil has a large diversity of the microbial community, which possesses plant growth-promoting activity as well as pathogen suppression. In the present study, the culturable microorganisms (fungi, bacteria and actinomycetes), in the rhizosphere of sixteen varieties of tropical tuber crops viz., sweet potato, elephant foot yam, cassava and yam were enumerated and compared; their role on suppression of Sclerotium rolfsii, the pathogen that causes collar rot in elephant foot yam was studied, and the ability of the organisms for growth promotion, nitrogen fixation, P and K solubilization was assessed, and the efficient antagonistic organisms were characterized by amplifying 16S rRNA. The microbial population varied significantly among the crops and varieties. Among one hundered and fifty organisms isolated and screened for pathogen suppression, ten bacterial and twelve actinomycete isolates completely inhibited the mycelial growth in the preliminary round of screening. Eight bacterial isolates chosen for further study based on consistency in pathogen suppression, exhibited IAA production while seven isolates showed nitrogen fixation. None of the bacterial isolates showed the formation of P or K solubilization zones in the selective media. Molecular studies based on 16S rRNA gene sequencing revealed that the most efficient antagonistic bacterial isolates with growth promotion potential were Bacillus spp. The six Bacillus species identified were Bacillus siamensis, B. amyloliquefaciens, B. pumilus, B. halotolerans, B. subtilis and B. altitudinis. Six out of eight efficient bacterial isolates were obtained from rhizosphere soils of sweet potato. The organisms, B.amyloliquefaciens and B.subtilis can serve as excellent bio-agents for pathogen suppression and growth promotion in tuber crops ecosystem.